The representation of Islam in the national geographic magazine cover of the Afghan girl: a multimodal analysis / Nadhratunnaim Abas and Roslina Abdul Aziz - Abas, Nadhratunnaim; Abdul Aziz, Roslina (2016)
The study is intended to delve into the portrayal of a Muslim identity that represents the constructed reality of Islam. Using Kress and van Leeuwen's (1996) Multimodal Analysis of reading visuals, it focuses on the semiotic properties of the Afghan Girl image in order to uncover its interpretation of the religion. The findings reveal that the identity of the girl as the "war-tom frontier" tends to represent Islam as a religion that is aligned with violence, fear, abandonment, miseries, and poverty.